The Relationship between Nominal Interest Rates and Inflation in Iraq - Helmy Ibraheem Menshad (مجلة الغري للعلوم الاقتصادية والادارية)
The main objective of this paper is to investigate the relationship between the nominal interest rates and inflation rate, and to verify the presence of the Fisher effect in Iraq during the period 2005M01 to 2016M12. Using the Johansen cointegration analysis and error correction model (VECM). The empirical results of this paper indicate that there is a long-run equilibrium relationship between nominal interest rates and expected inflation and existence of the partial Fisher effect in the long run . But, Fisher effect did not exist in the short run. Thus, there is the effectiveness of monetary policy in the short run, and the weakness of its effectiveness in the long run .